Effect of Psychotic Symptoms on Suicide Event in Patient with Severe Depression at Sanglah General Hospital - Ni Wayan, Kertiasih; Anak Ayu , Sri Wahyuni; Luh Nyoman Alit Aryani (Jurnal Psikiatri Surabaya, 2024)
Introductions: WHO states that the suicide rate in the world is still high; most of them had a previous depressive episode. In depressed patients with psychotic symptoms, psychomotor disturbances were more severe, feelings of guilt were higher, and there was an increase in suicidal ideation and attempts. Several studies have tried to find out whether there is an influence between psychotic symptoms and the incidence of suicide in patients with depressive disorders. However, the number of available studies is still limited and controversial. The purpose of this study was to determine the effect of psychotic symptoms on the incidence of suicide in patients with major depressive disorders. Methods: This is an observational analysis with a case-control approach. The sample was obtained from the Udayana Psychiatric Resident Duty Report in 2019 in a purposeful manner that already met the inclusion and exclusion criteria. Test the hypothesis using chi-square and logistic regression. Results: A total of 70 samples were used in this study. Chi-squared showed there was a relationship between psychotic symptoms and the incidence of suicide in patients with major depression (p = 0.016). Logistic regression showed that a history of drinking alcohol (OR 55.058; CI 2.975-1018.8; p = 0.007) and psychotic symptoms (OR 9.237; CI 1.86-45.875; p = 0.007) were shown to affect the incidence of suicide in patients with major depressive disorders. Conclusion: There is an effect of psychotic symptoms on the incidence of depression in patients with major depressive disorders.